PENGEMBANGAN BUKU TEKS PERADABAN PAKAIAN BERBASIS PROJECT BASED LEARNING UNTUK MENUMBUHKAN KARAKTER RASA INGIN TAHU - Zahra Rahmawati; Gregorius Ari Nugrahanta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Curiosity plays a crucial role in children’s cognitive development, supporting exploration, creativity, and learning. However, low curiosity can hinder academic performance and reduce learning motivation. This research aims to develop a Project-Based Learning (PBL) textbook on the theme of clothing civilization to enhance curiosity in children aged 10 to 12. Using a Research and Development (R&D) approach with the ADDIE model, ten certified elementary school teachers from different regions participated in the needs analysis, and ten validators served as expert reviewers. A group of students also participated in a limited trial of the textbook on clothing civilization. The study’s findings reveal that: 1) The ADDIE model effectively guided the creation of a textbook aimed at fostering curiosity; 2) The textbook’s quality was rated “Very Good,” scoring an average of 3.57 out of 4, with no revisions needed; and 3) The textbook significantly impacted curiosity development (p < 0.05) with a large effect size (r = 0.91), equating to an 85% effectiveness rate. The effectiveness level is categorized as high, with an N gain score of 97.437%.   Keywords: clothing civilization, project based learning, curiosity